Geographical distribution and oncogenic risk association of human papillomavirus type 58 E6 and E7 sequence variations - Chan, Paul K. S. (2013)
Fil: Chan, Paul K S. The Chinese University of Hong Kong. Faculty of Medicine. Department of Microbiology; China.